Association between Plasmodium falciparum parasite index and renal function in children - A Umboh; S Muljanto; J S Wibisono (Indonesian Pediatric Society, 2003)
Background Falciparum malaria is an acute systemic diseasethat can cause multi organ disorders including in kidney. The aimof this study was to figure out the association between P.falciparumparasite index and renal function in children by measuring ureum,creatinine, and glomerular filtration rate (GFR).Methods An analytic prospective study was conducted on all hos-pitalized falciparum malaria patients in the Department of ChildHealth, Manado Central General Hospital from November 2001-February 2002. Low parasitemia was defined if P.falciparum foundwas ≤100/100 fields and high parasitemia if >1/1 field. Data wereanalyzed by chi-square and student t–test.Results Among 34 patients, there were 11 with high parasitemiaand 23 with low parasitemia. There were 19 with increased ureumand 8 with increased creatinine. There was significant elevation ofureum in high parasitemia (n=10) compared to that in low para-sitemia patients (n=9) with p=0.004. The increase of serum creati-nine was found in 2 high parasitemia and in 6 low parasitemiapatients (p=0.611). Mean GFR was 107.63±30.62 in high and121.94±44.06 in low parasitemia patients (p=0.341).Conclusion There was a significant association betweenP.falciparum parasite index and serum ureum. But there was nosignificant association between parasite index and creatinine orGFR